2014
DOI: 10.1152/ajpheart.00571.2013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of activation pattern and active stress development on myocardial shear in a model with adaptive myofiber reorientation

Abstract: Pluijmert M, Bovendeerd PH, Kroon W, Prinzen FW, Delhaas T. Effects of activation pattern and active stress development on myocardial shear in a model with adaptive myofiber reorientation. Am J Physiol Heart Circ Physiol 306: H538 -H546, 2014. First published December 6, 2013 doi:10.1152/ajpheart.00571.2013.-It has been hypothesized that myofiber orientation adapts to achieve a preferred mechanical loading state in the myocardial tissue. Earlier studies tested this hypothesis in a combined model of left ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The assumption of homogeneity of transmural fibre strain has been challenged by experimental results from Ashikaga et al . in canine hearts under both sinus rhythm and epicardial pacing [ 36 , 37 ], and by finite element simulations showing transmural dispersion in time to onset of shortening [ 38 , 39 ]. In general, clinical and experimental measurements investigating transmural variation in strain patterns is difficult to obtain, and most studies in the literature represent averaged myofibre behaviour, as represented in the MultiPatch model.…”
Section: Discussionmentioning
confidence: 99%
“…The assumption of homogeneity of transmural fibre strain has been challenged by experimental results from Ashikaga et al . in canine hearts under both sinus rhythm and epicardial pacing [ 36 , 37 ], and by finite element simulations showing transmural dispersion in time to onset of shortening [ 38 , 39 ]. In general, clinical and experimental measurements investigating transmural variation in strain patterns is difficult to obtain, and most studies in the literature represent averaged myofibre behaviour, as represented in the MultiPatch model.…”
Section: Discussionmentioning
confidence: 99%
“…In the experimental results (Pluijmert et al. 2014), the total amplitude of is and the gradient in at end ejection is apex–mid–base. In the initial state in the model, the total amplitude of is 0.35 with a base–mid–apex gradient at end ejection.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown that including active stress development perpendicular to the myofiber direction influences the amplitudes of the developed , but not the gradient of after reorientation (Pluijmert et al. 2014 ). The effect of sheet orientation and orthotropy needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…32 This adaptation in fibre orientation leads to a more homogeneous strain distribution and improved pump function. Figure 4 shows preliminary results of activation times and distribution of mechanical work in a normal heart and hearts with LBBB and with CRT.…”
Section: Mechanical Modelsmentioning
confidence: 99%